2016
DOI: 10.1177/0300060516674353
|View full text |Cite
|
Sign up to set email alerts
|

The association of uric acid with leukoaraiosis

Abstract: ObjectiveTo explore the possible correlation between uric acid levels and leukoaraiosis (LA).MethodsThis cross-sectional study enrolled patients who presented with some neurological discomfort (e.g. dizziness, headache, mild cognitive impairment). Potential demographic and clinical risk factors associated with LA, including sex, age, hypertension, diabetes mellitus, smoking, alcohol consumption, dyslipidaemia, plasma fibrinogen, D-dimer, uric acid, and homocysteine, were investigated using univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Therefore, an automated WMLs volumetric/quantitative analysis is suggested to be applied in the epidemiology study of LA in future. In addition, the association analysis of several recently reported risk factors, such as C-reactive protein, uric acid, thyroid function and vitamin B12, obesity index-body mass, and working and living conditions, [ 43 45 ] with the risk of LA were not conducted in this study since these parameters were not available for all of subjects. The last but not the least is the limitation that both the percent of subjects with stroke among this study cohort and the relationship of stroke and LA could not be assessed because the information is inaccessible for a large portion of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an automated WMLs volumetric/quantitative analysis is suggested to be applied in the epidemiology study of LA in future. In addition, the association analysis of several recently reported risk factors, such as C-reactive protein, uric acid, thyroid function and vitamin B12, obesity index-body mass, and working and living conditions, [ 43 45 ] with the risk of LA were not conducted in this study since these parameters were not available for all of subjects. The last but not the least is the limitation that both the percent of subjects with stroke among this study cohort and the relationship of stroke and LA could not be assessed because the information is inaccessible for a large portion of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Lifelong exposure to dietary, environmental, physiologic, behavioral, and pharmacological factors exposes brain tissue to oxidative injury. As a result, oxidative stress is important for many neurologic disorders including migraine [10][11][12][13]. Some studies have reported a significant correlation between oxidative changes and migraine, while some have not found a significant correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine threshold is linked to a sensitive balance between oxidative phosphorylation occurring in mitochondria and stimulation and inhibition in the central nervous system [8,16]. The end-product of endogenous and exogenous purine catabolism of uric acid (UA) protects erythrocytes from lipid peroxidation and hemoglobin from peroxide oxidation and at normal levels scavenges toxic reactants, showing endogenous antioxidant activity [11,13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…12 UA has a strong endogenous antioxidant effect in some oxidative stress-induced neurodegenerative diseases and is also involved in numerous disorders, including cardiovascular disease, obesity, diabetes, leukoaraiosis, as well as inflammation. 2,3,[13][14][15][16] Although UA may exert an important function in protecting neurons from inflammatory injuries, it is still not clear what the role of UA is in brain injury patients. Some studies have found that a low GCS was related to a low UA level in patients with TBI, suggesting that UA may have some function in the recovery from consciousness.…”
Section: Renal Filtration and Reabsorption Assessmentmentioning
confidence: 99%